Predicted mortality from malignant mesothelioma among women exposed to blue asbestos at Wittenoom, Western Australia - Reid, Alison; Berry, G.; Heyworth, J.; De Klerk, N.; Musk, A. (BMJ Group, 2009)
Introduction: Nearly 3000 women and girls were documented to have lived at the blue asbestos mining and milling town of Wittenoom in Western Australia between 1943 and 1992. Eight per cent of deaths among these women to the end of 2004 have been from malignant mesothelioma of the pleura. Aim: To predict future mortality from mesothelioma to 2030 in this cohort. Methods: Mesothelioma mortality rates incorporating parameters for cumulative exposure, a power of time since first exposure and annual rates of fibre clearance from the lung were calculated from maximum likelihood estimates. These rates plus age specific mortality rates for Western Australian females incorporating an excess lung cancer risk were then applied to all Wittenoom cohort women surviving to the end of 2004, in yearly increments, to predict the future numbers of cases of mesothelioma to 2030. Results: There were 40 deaths from mesothelioma among the Wittenoom women to the end of 2004. Using a range of models that incorporate time since first exposure, competing risks from other diseases, latency periods and clearance of mesothelioma from the lungs we predict 66 (lowest estimate) to 87 (highest estimate) deaths from mesothelioma until 2030. This represents one and a half to two and a half times the number of deaths that have already occurred to the end of 2004. Conclusion: The high toll from mesothelioma in this cohort of women and girls will continue well into the future.